Research Progress on Treatment of Alcohol-Free Produced Water in Changqing Gas Field - Cui, Jiahao; He, Zhiying; Zha, Guangping; Fan, Pengjun; Cheng, Xin; Yang, Juan; Zhang, Yongda; Zhao, Mengtian; Zhang, Luwen; Zhang, Chi; Ma , Yun (Scientific Journal of Technology, 2025)
Changqing gas field is the largest oil and gas field in China. The discharge of alcohol-free produced water continues to grow with the expansion of mining scale. This kind of wastewater has the remarkable characteristics of ’ high turbidity, high salinity, strong corrosion and low pH value ’. The composition is complex and the treatment is difficult. The national environmental protection policy has tightened the promotion of wastewater treatment from underground reinjection to ground standard treatment and comprehensive utilization. Efficient treatment and resource utilization have become the key to green mining of gas fields. In this paper, the water quality characteristics and three treatment methods of produced water without alcohol in gas field are systematically sorted out. The five main treatment technologies of physics, chemistry, physics and chemistry, biology and compound, as well as the special treatment technologies such as Fenton method and double alkali system method and the reuse technology of fracturing flowback fluid are expounded in detail. The optimization measures of corrosion control are analyzed, and the future development direction of technology is prospected. This review can provide a reference for the efficient treatment and resource utilization of alcohol-free produced water in Changqing gas field and similar gas fields.